2022
DOI: 10.1371/journal.pbio.3001733
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep loss leads to the withdrawal of human helping across individuals, groups, and large-scale societies

Abstract: Humans help each other. This fundamental feature of homo sapiens has been one of the most powerful forces sculpting the advent of modern civilizations. But what determines whether humans choose to help one another? Across 3 replicating studies, here, we demonstrate that sleep loss represents one previously unrecognized factor dictating whether humans choose to help each other, observed at 3 different scales (within individuals, across individuals, and across societies). First, at an individual level, 1 night o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 125 publications
0
26
0
Order By: Relevance
“…More recently, in a thought provoking set of studies, sleep loss and sleep's diminished quality and or quantity, which indeed present one of the important features of OSA, have also been linked to diminished altruism (Ben Simon et al, 2022). Specifically, the authors argued that sleep loss represents one previously unrecognized factor that may dictate whether humans choose to help each other, which they based on their observations at three different scales, within individuals, across individuals, and across societies (Ben Simon et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in a thought provoking set of studies, sleep loss and sleep's diminished quality and or quantity, which indeed present one of the important features of OSA, have also been linked to diminished altruism (Ben Simon et al, 2022). Specifically, the authors argued that sleep loss represents one previously unrecognized factor that may dictate whether humans choose to help each other, which they based on their observations at three different scales, within individuals, across individuals, and across societies (Ben Simon et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in a thought provoking set of studies, sleep loss and sleep's diminished quality and or quantity, which indeed present one of the important features of OSA, have also been linked to diminished altruism (Ben Simon et al, 2022). Specifically, the authors argued that sleep loss represents one previously unrecognized factor that may dictate whether humans choose to help each other, which they based on their observations at three different scales, within individuals, across individuals, and across societies (Ben Simon et al, 2022). For instance, in one of the studies, one night of sleep loss was shown to trigger the withdrawal of help from one individual to another, with the associated fMRI findings showing deactivation of key nodes within the social cognition brain network that facilitate prosociality (Ben Simon et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…People often change their evaluations and opinions upon learning about their peers’ evaluations and choices, i.e., social learning (Berns et al, 2010; Campbell-Meiklejohn et al, 2010; Kendal et al, 2018). Moreover, sleep impacts social and non-social decision-making (Ben Simon et al, 2022; Dickinson & McElroy, 2017; Holbein et al, 2019; Venkatraman et al, 2011). Combining the social learning paradigm with sleep-based targeted memory reactivation (TMR), we investigated whether reactivating the daytime social learning experience during non-rapid-eye-movement (NREM) sleep could further promote social learning-induced evaluation changes.…”
Section: Discussionmentioning
confidence: 99%
“…The transitions into and out of DST not only influence health and safety, but can also impact human behavior in general. People are less generous in the week after DST begins, as measured by charitable donations [34 ▪▪ ]. On the job procrastination is increased with poor sleep, particularly in later chronotypes, and this effect is amplified with the start of DST [35].…”
Section: Introductionmentioning
confidence: 99%